Thermal and entropy analyses on buoyancy-driven flow of nanofluid inside a porous enclosure with two square cylinders: Finite element method - Dogonchi, A. Sattar; Mishra, S.R.; Chamkha, Ali J.; Ghodrat, M.; Elmasry, Yasser; Alhumade, Hesham (Case studies in thermal engineering, 2021)
The present article reveals the study of heat transfer via buoyancy-driven flow and entropy generation of magnetic Fe3O4–H2O nanoliquid inside a porous enclosure using two square cylinders. The shape factor of diverse particle shapes may well be also considered. Numerical technique called FEM is implemented for the transformed governing equations. Results of Nusselt number, entropy generation, Bejan number along with the streamlines and the isotherms are obtained for disparate contributing parameters. Validation with earlier studies exhibits an excellent agreement in particular case and findings portray that entropy generation rises with growing Hartmann number and mounting Rayleigh number could overshoot the velocity gradient within the enclosure. •Entropy and free convection of magnetic nanofluid in a wavy porous enclosure that includes two square cylinders are analyzed.•The dimensions of the square cylinders may well be changeable that could considerably affect the hydrothermal features.•Finite element method (FEM) might well be exerted to solve the governing equations.